2009
DOI: 10.1093/hmg/ddp167
|View full text |Cite
|
Sign up to set email alerts
|

TRIM32 is an E3 ubiquitin ligase for dysbindin

Abstract: Mutations in the gene encoding tripartite motif protein 32 (TRIM32) cause two seemingly diverse diseases: limb-girdle muscular dystrophy type 2H (LGMD2H) or sarcotubular myopathy (STM) and Bardet–Biedl syndrome type 11(BBS11). Although TRIM32 is involved in protein ubiquitination, its substrates and the molecular consequences of disease-causing mutations are poorly understood. In this paper, we show that TRIM32 is a widely expressed ubiquitin ligase that is localized to the Z-line in skeletal muscle. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 48 publications
4
123
0
Order By: Relevance
“…The interaction of all these 14-3-3 isoforms with FLAG-TRIM32 were stimulated by coexpression of cPKA in HEK293 cells (Fig. 2C), a cell line widely used in the study of TRIM32 interaction and localization (Kano et al, 2008;Locke et al, 2009;Ryu et al, 2011). Phosphate incorporation into TRIM32 under these conditions was confirmed using phospho-PKA substrate antibodies (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The interaction of all these 14-3-3 isoforms with FLAG-TRIM32 were stimulated by coexpression of cPKA in HEK293 cells (Fig. 2C), a cell line widely used in the study of TRIM32 interaction and localization (Kano et al, 2008;Locke et al, 2009;Ryu et al, 2011). Phosphate incorporation into TRIM32 under these conditions was confirmed using phospho-PKA substrate antibodies (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Like many TRIMs, TRIM32 has two potential autoregulatory properties. One is that it often self-associates and forms insoluble high-molecular-mass puncta called cytoplasmic bodies (CBs) when transiently expressed in cells (Albor et al, 2006;Locke et al, 2009). Although the role of CBs in TRIM32 functions is not fully understood, recent studies, particularly with TRIM19 and TRIM5, have suggested that CBs may function as aggresome precursors or storage compartments that maintain the proper level of soluble free TRIM proteins (Song et al, 2005;Diaz-Griffero et al, 2006) or exchange the proteins between CBs and a more diffuse cytoplasmic fraction (Campbell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 TRIM32 ubiquitinates dysbindin that may contribute to TRIM32's role in skeletal muscle and neuronal cell differentiation. 17 Most recently, p73 was reported to upregulate the basal levels of TRIM32, and furthermore, TRIM32 ubiquitinates p73 in neuronal cells, which might contribute to TRIM32's function in neuronal development and differentiation. 41 The regulation of TRIM32 by p53 and p73 appears to be different and highly context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM32 ubiquitinates dysbindin that may contribute to TRIM32's role in skeletal muscle and neuronal cell differentiation. 17 TRIM32 ubiquitinates NF-kB inhibitor Piasy and tumor suppressor Abi2, which may contribute to TRIM32's role in tumorigenesis. 16,18 In this study, we identified TRIM32 as a novel p53 target and negative regulator for p53.…”
mentioning
confidence: 99%
See 1 more Smart Citation